2008
DOI: 10.1111/j.1530-0277.2008.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Acamprosate and MPEP on Ethanol Drinking‐in‐the‐Dark in Male C57BL/6J Mice

Abstract: These results support the hypothesis that mGluR5 signaling plays a role in excessive ethanol intake in DID and suggest DID may have value for screening novel compounds that reduce overactive glutamate signaling for potential pharmaceutical treatment of excessive ethanol drinking behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 44 publications
(78 reference statements)
2
63
2
Order By: Relevance
“…Limitations include that while showing similar treatment effects as the selective mGluR5 antagonist MPEP (20 mg/ kg) in the drinking-in-the-dark mouse model, acamprosate (300 mg/kg) was significantly less potent (Gupta et al 2008). Acamprosate has poor oral bioavailability (about 11%) and low intestinal permeability requiring high and frequent dosing (Forest Pharmaceuticals Inc 2005), a requirement which may limit the tolerability of the drug as we found given gastrointestinal distress in 2 of 3 patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Limitations include that while showing similar treatment effects as the selective mGluR5 antagonist MPEP (20 mg/ kg) in the drinking-in-the-dark mouse model, acamprosate (300 mg/kg) was significantly less potent (Gupta et al 2008). Acamprosate has poor oral bioavailability (about 11%) and low intestinal permeability requiring high and frequent dosing (Forest Pharmaceuticals Inc 2005), a requirement which may limit the tolerability of the drug as we found given gastrointestinal distress in 2 of 3 patients.…”
Section: Discussionmentioning
confidence: 97%
“…Acamprosate and MPEP have both been associated with increased sedative effects of alcohol and reduced alcohol withdrawal in mice; no effects of acamprosate or MPEP were noted in mGluR5 knockout mice (Blednov and Adron Harris 2008). Gupta and colleagues (2008) demonstrated that acamprosate and MPEP both dose dependently reduced ethanol drinking in the drinking-inthe-dark mouse model (Gupta et al 2008). In a conflicting report, at concentrations typically achieved in humans, acamprosate did not modulate the function of many neuroreceptors, including mGluR receptors, in an electrophysiological study in Xenopus oocytes (Reilly et al 2008).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Taken together, these results suggest that the increased sensitivity to the sedative/hypnotic effects of ethanol seen in ClockD19 mice may be because of a hyperglutamatergic system and are likely not due to differences in GABAergic transmission. Gupta et al (2008) reported that glutamatergic signaling has a role in binge-like ethanol drinking in the drinking in the dark (DID) paradigm, where they reported that mice pretreated with acamprosate or MPEP (an mGluR5 antagonist) exhibited decreased DID. Perhaps, the altered glutamatergic tone indirectly measured by ketamine LORR and directly measured and described by Beaulé et al (2009) in ClockD19 mice would lead to increased binge-like ethanol drinking in the DID paradigm.…”
Section: Clockd19 Mice Exhibit Augmented Responses To the Sedative Efmentioning
confidence: 99%
“…Acamprosate has pleiotropic effects impacting glutamate and GABA neurotransmission (34). Its mGluR5 antagonist effect has been demonstrated in animal models of alcoholism (30,35,36) followed by two pilot clinical trials conducted by Erickson et al 2011 and 2013 in patients with FXS + ASD finding that 75% of the sample responded to treatment exhibiting improvement in social behavior, hyperactivity and communication skills (33). This medication should be studied further not only in those with FXS but also to treat the alcoholism that can occur in this disorder.…”
Section: Casementioning
confidence: 99%